2022
DOI: 10.1002/1873-3468.14303
|View full text |Cite
|
Sign up to set email alerts
|

Improved synthesis of an ergothioneine PET radioligand for imaging oxidative stress in Alzheimer’s disease

Abstract: To study ERGO biodistribution and detect oxidative stress in vivo, we report an efficient and reproducible preparation of [ 11 C]-labeled ERGO PET radioligand based on protecting the histidine carboxylic group with a methyl ester. Overall, this new protection approach using methyl ester improved the chemical yield of a 4-step reaction from 14% to 24% compared to the previous report using t-butyl ester. The [ 11 C]CH 3 methylation of the precursor provided the desired product with 55 AE 10% radiochemical purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recently, we reported that longitudinal consumption of Ergo reduced Aβ plaques in the brain cross-sections, oxidative stress, and rescued glucose metabolism in a 5XFAD mouse model ( Whitmore et al, 2022 ). In our previous work, an efficient and reproducible preparation of [ 11 C]-labeled Ergo PET radioligand to detect threshold levels of oxidative stress in a preclinical animal model of AD was also reported ( Behof et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that longitudinal consumption of Ergo reduced Aβ plaques in the brain cross-sections, oxidative stress, and rescued glucose metabolism in a 5XFAD mouse model ( Whitmore et al, 2022 ). In our previous work, an efficient and reproducible preparation of [ 11 C]-labeled Ergo PET radioligand to detect threshold levels of oxidative stress in a preclinical animal model of AD was also reported ( Behof et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…(Supplementary Data on the analysis methods, Figure S3). Recently, our [ 11 C]ERGO PET radioligand has been demonstrated as an imaging biomarker for oxidative stress in a mouse model of lipopolysaccharides (LPS) [32] and 5XFAD mice [38]. Thus, in this study, [ 11 C]ERGO PET radioligand was used to assess the fluctuation in oxidative stress with respect to the ERGO therapy.…”
Section: Longitudinal Consumption Of Ergo Mitigates Aβ Aggregation In...mentioning
confidence: 99%
“…Perhaps, however, deficiency diseases are staring us in the face: low blood or plasma levels of ET are correlated with increased risk of frailty [16][17][18], cardiovascular disease [19], mild cognitive impairment [18,[20][21][22], dementia [22,23] and Parkinson's disease [24]. Indeed, ET has many neuroprotective properties [4,5,18,26,27], as reviewed in detail in this special issue [18,25,26]. Consistent with a key protective role of ET against the development of age-related diseases, higher dietary consumption of mushrooms, a rich source of ET [9], is associated with lower disease risk [28][29][30][31].…”
mentioning
confidence: 99%